AB0377 CLINICAL SIMILARITY OF ABP 710 WITH INFLIXIMAB (REFERENCE PRODUCT) IN SUBJECTS WITH MODERATE TO SEVERE RHEUMATOID ARTHRITIS. (June 2019) - Genovese, Mark C.; Sanchez-Burson, Juan; Oh, Myungshin; Balázs, éva; Neal, Jeffrey; Fanjiang, Gary; Cohen, Stanley
Abstract : Background: ABP 710 is being developed as a biosimilar to infliximab. Both ABP 710 and infliximab reference product (RP) inhibit tumor necrosis factor-alpha and have been shown to be structurally and functionally similar in analytical assessments. In a phase 1 clinical pharmacokinetic (PK) study both were shown to be bioequivalent for PK parameters. The final step in the demonstration of biosimilarity is a comparative phase 3 clinical trial in a representative indication Objectives: The objective of this study was to evaluate the similarity of ABP 710 compared to RP with respect to efficacy and safety. Methods: In this multicenter, randomized, double-blind study, the efficacy and safety of ABP 710 was compared with the RP in subjects with moderate to severe rheumatoid arthritis. Subjects were maintained on a stable 7.5 to 25 mg/week dose of methotrexate and received 3 mg/kg infusions of the investigational products (IPs) at predetermined intervals. The primary endpoint of the study was risk difference (RD) of ACR20 at week 22; secondary endpoints included DAS28-CRP and safety at week 22. The confidence intervals (CI) for RD of ACR20 were estimated using the intention-to-treat analysis set with non-responder imputation based on the subject's randomized treatment. Clinical equivalence was evaluated by comparing the 2-sided 90% CI with the equivalence margin of (-15%, 15%) of the RD of ACR20. For change of DAS28-CRP at week 22 from baseline, the CI of the mean difference was estimated using an analysis of covariance model with relevant baseline values and stratification factors as covariates. Results: Of the 558 randomized subjects, 556 were treated (ABP 710 n=278; RP n=278). For ACR20, the RD was 9.3% and the lower bound of the 90% CI (2.67%, 15.96%) was within the pre-specified criteria, thus confirming non-inferiority; the upper bound slightly exceeded the pre-specified criteria such that superiority cannot be ruled out statistically. In post-hoc analysis when the impact of random imbalance in baseline demographic and disease characteristic between the 2 treatment arms was adjusted, the RD was reduced to 7.18% and the 90% CI was narrowed to (0.75%, 13.62%). Results of change of DAS28-CRP at week 22 showed a difference in mean change from baseline of -0.01 with 90% CI of (-0.20, 0.17). Since this difference is less than the suggested EULAR threshold of 0.6 for clinically meaningful difference, the result supports both non-inferiority and non-superiority. Through week 22, percentage of subjects reporting any serious adverse events was 4.1 (ABP 710=3.2; RP=5.0) and the binding/neutralizing antibody positive post-baseline in subjects were 58.9/19.4 (ABP 710=57.1/18.0; RP=60.6/20.8). Conclusion: The results of this study indicate that ABP 710 is similar to the RP. Although we were unable to statistically confirm non-superiority, post-hoc analysis is supportive of non-superiority. The DAS28-CRP difference of less than 0.6 is believed to not be clinically meaningful. These efficacy and safety results support similarity between ABP 710 and infliximab RP. Acknowledgement: Sonya Lehto and Monica Ramchandani for medical writing. Study investigators and patients Disclosure of Interests: Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm, Juan Sanchez-Burson Speakers bureau: Lilly, Janssen, Pfizer, MyungShin Oh Shareholder of: Amgen, Employee of: Amgen, éva Balázs Grant/research support from: Celltrion, Inc., Consultant for: Merck and Amgen, Jeffrey Neal Consultant for: Investigator Amgen, Gary Fanjiang Shareholder of: Amgen, Employee of: Amgen, Stanley Cohen Grant/research support from: AbbVie, Amgen Inc., AstraZeneca, Biogen-IDEC, Bristol Meyer Squibb, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Merck, and Roche, Consultant for: Abbvie, Amgen, AstraZeneca, Biogen-IDEC, Bristol Meyer Squibb, Genentech, Janssen, Lilly, Novartis Pfizer, Merck and Roche